The Influence of Motivation, Compensation, and Competency on Employee Performance Mediated by Job Satisfaction (Case Study at Lembaga Penjamin Simpanan) - Fitriany, Netty; Mudjijah, Slamet (International Journal of Finance Research, 2024)
This research aims to analyze motivation, compensation, and competence on employee performance as mediated by job satisfaction at the Deposit Insurance Corporation. This research uses a survey method with a sample of 100 people using a proportional stratified random sampling technique. The data collection technique uses a questionnaire whose validity and reliability have been tested. The data analysis technique uses the Partial Least Square (PLS) application version 3.2.9. by evaluating the outer model, the inner model, and path analysis tests. The research results provide conclusions: (1) Motivation has no significant effect on employee performance; (2) Compensation has a significant effect on employee performance; (3) Competency has a significant effect on employee performance; (4) Motivation has no significant effect on job satisfaction; (5) Compensation has a significant effect on job satisfaction; (6) Competency has a significant effect on job satisfaction; (7) Job satisfaction has no significant effect on employee performance; (8) The influence of motivation on employee performance cannot be mediated by job satisfaction; (9) The effect of compensation on employee performance cannot be mediated by job satisfaction; (10) The influence of competency on employee performance cannot be mediated by job satisfaction; (11) The coefficient value of the determinant ( ) of the Job Satisfaction construct is 0.649, indicating that the influence of Motivation, Compensation, and Competence constructs on Job Satisfaction is 64.9%; (12) The coefficient value of the determinant ( ) of the Employee Performance construct is 0.640, indicating that the influence of Motivation, Compensation, and Competence Job Satisfaction constructs on Employee Performance is 64%.